Using Task-Based Language Teaching (TBLT) to Improve Junior High School Students’ Participation and Reading Comprehension Achievement - Rainia Adina Winda Rosa; Zakiyah Tasnim; Siti Masrifatul Fitriyah (EFL Education Journal, 2021)
This classroom action research, with one cycle, was aimed at improving junior high school students’ participation and reading comprehension achievement by using the Task-Based Language Teaching (TBLT) approach. Observation, pre-test and post-test were used to collect the data. The collected data were analyzed by using descriptive statistics with a percentage formula. The research results showed that the student's participation during the teaching and learning process of reading comprehension by applying TBLT improved from 73.9% in the second meeting, to 90 % in the third meeting, and to 100% in the fourth meeting. In addition, the students’ reading comprehension achievement also improved from 35% in the pre-test to 81% in the post-test. Therefore, junior high school English teachers are suggested to apply TBLT in teaching reading comprehension.